Confession and Community in Seventeenth-Century France : Catholic and Protestant Coexistence in Aquitaine - Hanlon, Gregory (University of Pennsylvania Press, 2016)
Examines the tolerance between Catholics and Protestants in a period when vicious sectarian strife was the rule of the day. Tolerance here means more than mere coexistence but a daily interaction between people without regard for their faith.
Keywords: Catholic Church -- France -- Aquitaine -- History -- 17th century.; Catholic Church -- History -- 17th century.; Église catholique -- Histoire -- 17e siècle.; Catholic Church; Reformed Church -- France -- Aquitaine -- History -- 17th century.; Aquitaine (France) -- Church history.; Église réformée -- France -- Aquitaine -- Histoire -- 17e siècle.; RELIGION -- Christianity -- History.; Reformed Church; France -- Aquitaine; 1600-1699; Church history; History